2019
DOI: 10.5539/jas.v11n18p140
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Simulation of the CERES-Sorghum and CERES-Maize Models for Crops in the Central-West Region of Paraná State

Abstract: Simulation models have been widely used to generate yield data by forecasting climate variables and changes in growing seasons. The aim of this study was to calibrate genetic coefficients and simulate growth, development and yield in maize and sorghum crops based on historical meteorological data for the municipality of Juranda (2007 to 2013), in the central-west region of Paraná State, Brazil. Treatments were established based on three planting dates in two growing seasons for a group of super earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
1
0
0
1
Order By: Relevance
“…The rsquare value of 0.74 and 0.76 was observed for CO 30 and K 12 varieties, respectively. This finding was corroborated with the findings of Vieira et al [14] and Tesfaye et al [15] who reported r square (r 2…”
Section: Fig 1 Methodology Of Dssat-ceres Modulesupporting
confidence: 90%
“…The rsquare value of 0.74 and 0.76 was observed for CO 30 and K 12 varieties, respectively. This finding was corroborated with the findings of Vieira et al [14] and Tesfaye et al [15] who reported r square (r 2…”
Section: Fig 1 Methodology Of Dssat-ceres Modulesupporting
confidence: 90%
“…Soltangheisi et al (2019), avaliaram o efeito da vinhaça sobre a adsorção de fósforo em amostras da fração argila de dois solos Latossolo Vermelho e Gleissolo Melânico, onde puderam concluir que o tratamento da fração argila com vinhaça reduziu a adsorção de P, possivelmente devido ao bloqueio dos sítios de adsorção de P pelos compostos orgânicos da vinhaça e, também, pelo aumento da carga líquida negativa da fração argila. Vieira et al (2019) utilizando a cultura do sorgo forrageiro adubado com resíduo tratado originário de fecularia em lisímetros instalados em campo, observaram redução do teor de fósforo disponível no solo com a elevação das doses de manipueira, onde o menor teor de P (1,63 mg dm -3 ) foi encontrado na maior dose de manipueira (900 m 3 ha -1 ).…”
Section: Resultsunclassified